A History in Blue Pencil: Cyril Monk's Performance Annotations and a Bygone Musical Style. Issue 1 (2nd January 2022) - Russoniello, Julia
Abstract: Australian violinist Cyril Monk (1882–1970) was described in the 25 July 1920 edition of Sydney's Sun newspaper as 'one of the best-known violinists in the Commonwealth'. Although he is an unfamiliar name today, Cyril Monk was a prolific recitalist, chamber musician, orchestral leader, and lecturer, as well as a pioneer in the presentation of Australian music. As Monk's early musical training and most of his long professional career took place in Sydney, his individual playing style offers a perspective on the performing traditions of this time and place. Due to the scarcity of recordings of Australian artists before 1940, how Cyril Monk and violinists of his generation sounded is a mystery today. This article surveys Cyril Monk's published editions as well as recently discovered annotated scores to document aspects of a string performance style which has been all but forgotten. Extant materials and a surviving recording from Cyril Monk's musical life provide a snapshot of his individual playing style and of the performance culture in which he operated.